A Minskyan account of emerging currencies dynamics. Issue 4 (2nd October 2019) - Ramos, Raquel A.
Abstract: The currencies of a few emerging market economies (EMEs) have been following a specific dynamic since the early 2000s: They are strongly subordinated to international financial conditions, appreciating in moments of tranquility and presenting sharp depreciations in peaks of uncertainty. What is the mechanism behind it? To answer this question, this article applies the Minskyan framework to the context of money managers and their portfolio allocation decisions. The approach provides a detailed account of the mechanisms of the appreciation phase, thus complementing the emerging currencies' literature that is focused on crisis episodes. The result is a dynamic characterized by deviation-amplifying systems—the opposite of the mainstream view where fundamentals lead to an equilibrium-seeking mechanism. Apart from these contributions to the exchange rate literature, it enriches the Minskyan literature for providing a broader reading of the original framework that allows it to be transposed to a larger set of contexts and for identifying the main elements to be translated in an analysis of a different context.